IMPLEMENTASI COMPUTATIONAL THINKING PADA KURIKULUM MERDEKA MENGGUNAKAN METODE UNPLUGGED PROGRAMMING ACTIVITY (UPA) - Sutojo, T.; Rustad, Supriadi; Akrom, Muhamad; Herowati, Wise (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
The application of Computational Thinking (CT) in the Kurikulum Merdeka is one way to strengthen fundamental competencies and holistic understanding in education. CT skills can be taught through Unplugged Programming Activities (UPA), which is an approach to teaching CT skills without using computer tools. This approach is appropriate for schools that do not have adequate technological infrastructure and for the little ones, namely students under 9 years of age. This service aims to provide UPA method training for teachers at Gaussian Kamil School (GKS) so that it can be applied to the Merdeka Curriculum at GKS. The UPA activity materials used were the games